The illusion of deconstruction: Orientalism and Japanese representation in Wes Anderson's Isle of Dogs (2018) - Prawira, Mentari Putrirahayu; Ramadhan, Iusvaldio; Alivin, Moh. Zamil (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
Said stated that Orientalism is the domination of the West over the East. Orientalism emerged after many trips made by European countries, causing the Orient or East to be exploited by the West. One form of exploitation is present in the film industry, as presented by the animation Isle of Dogs (2018) by Wes Anderson. This research uses Boggs and Petrie's (2018) cinematography theory to look at the symbols presented through places and characters in the film. Stuart Hall's representation theory (1997) is used to interpret symbols which are representations of Japanese culture. This research shows dichotomies used in the film, such as Japanese and English language, humans, and animals (dogs), modernity and traditional, active American students and passive Japanese students as symbol or representation of West and East which is an element of orientalism. The result of this research shows that this film has an attempt to destroy the idea of orientalism, but the representation of Japan presented in this film confirms the idea of orientalism itself. Hence, it can be said that this film failed to deconstruct the orientalism.